Effect of Monetary Policy on Nigerian Stock Market Performance - AlajekwuUdoka Bernard, PhD. Student, Assoc. Prof. Clem Nwakoby, (International Journal of Scientific Research and Management (IJSRM), 2016)
The study investigated the effect of monetary policies on stock market performance in Nigeria. The study covered a period of 28 years (1986 – 2013). Data were generated from the Central Bank of Nigeria Statistical Bulletin, 2013 edition. The ex post facto research design was adopted. The method of data analyses used are b the Johansen co-integration, OLS and granger causality tests. All Share Index was used as the indicator of stock market performance (ASI) while the explanatory variables includedMonetary Policy Rate (MPR), Treasury bill rate (TBR), Lending interest rate (INT), Liquidity ratio (LR) and deposit rate (DR).  The co-integration result indicates that there is long run relationship between monetary policy and stock market performance in Nigeria. The OLS regression result showed that monetary policy significantly explains 53% of changes stock market performances in Nigeria.  However, Monetary Policy Rate (MPR) has insignificant positive effect on All Share Index (ASI) while Lending Rate (INT) has significant positive effect on All Share Index (ASI). Furthermore, Treasury Bill Rate (TBR) and Liquidity Ratio (LR) have insignificant negative effect on All Share Index (ASI) in Nigeria; and Deposit Rate (DR) has a significant negative effect on All Share Index (ASI) in Nigeria. The granger causality analyses showed that All Share Index (ASI) has no causal relationship with monetary policy rate (MPR), Treasury bill rate (TBR), and liquidity ratio (LR) in Nigeria. However, All Share Index (ASI) has causal relationship with lending and deposit rates in Nigeria. This indicate that monetary policy has the potential (53%) to influence the stock market, but the causality analyses showed that monetary policy cannot influence stock market performance but rather stock market performance has influenced the direction of monetary policy in Nigeria through lending and deposit rates.  Among others, the study recommended that policy makers in Nigeria must be mindful of the unidirectional causality from stock market to the monetary policy variables in formulating monetary policies. This will enable them to sufficiently and timely adjust Nigerian stock market to economic conditions in the country